Treatment of recalcitrant orbital inflammatory syndrome with plasmapheresis therapy. Issue 1 (8th January 2020) - Rodriguez Torres, Yasaira; Azad, Fereshteh; Lin, Xihui
Abstract : Refractory idiopathic orbital inflammation (IOI) represents a management challenge due to its significant proportion of treatment failures. Currently, there are no established guidelines for recalcitrant IOI and majority of immunosuppressive agents have resulted in variable outcomes. Advancements of plasmapheresis therapy can play a significant role in ophthalmological diseases. This treatment has shown to produce a satisfactory therapeutic response in immune-mediated neurological conditions. In this case report, we share our successful experience with the use of plasmapheresis therapy in a patient with recalcitrant IOI.